Empowerment Training Pastoral Capacity of Pastors in Donggala and Sumba: Pelatihan Pemberdayaan Kapasitas Pastoral Pendeta di Donggala dan Sumba - Garey, Evans; Paramita, Widia (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The pastor plays a significant role in the pastoral care of his people, not only in the religious/spiritual area, but also in the area of ​​daily life. Pastors need knowledge and skills regarding the development of human life to be effective in serving. This training aimed to increase the pastors’ pastoral capacity in accompanying individual parishioners. Participants were priests in Donggala and Sumba. Training was given for two days in Jakarta, about human development from infants to the elderly. The methods provided were lectures, workshops, discussions, questions and answers. Measurement of participants' learning levels was carried out using Kirkpatrick's three levels. The results showed that participants were satisfied, experienced an increase in knowledge from before to after training, and would carry out the actions they had learned during the training. The follow-up to this training is to measure the implementation of the training results in the pastors' workplaces.